Where Did the Agricultural Nonpoint Source Trades Go? Lessons from Virginia Water Quality Trading Programs1. (28th August 2017) - Stephenson, Kurt; Shabman, Leonard
Abstract: Governmental agencies, nongovernmental organizations, and agricultural organizations promote water quality trading programs as an innovative policy to engage agricultural producers in conservation activities. Cost analyses suggest regulated sources can reduce compliance costs by purchasing agricultural nonpoint source credits. Yet, such "point‐nonpoint" trades are rare. This article assesses the demand for agricultural nonpoint sources in well‐developed nutrient trading programs in Virginia for industrial and municipal wastewater treatment plants, municipal stormwater programs, and land developers. Evidence suggests nutrient trading programs in Virginia will not stimulate investments in pollutant reduction practices on working agricultural lands. The lack of demand for agricultural nonpoint source credits can be attributed to a substantial degree to the design features and incentives present in multiple overlapping regulatory programs. The legal setting that dampens regulated source demand for nonpoint source credits in Virginia is broadly representative of conditions found elsewhere in the United States.